Architectural conservation, Bangladesh - Imamuddin, Abu H. (Asiatic Society of Bangladesh : Distributor, Academic Publishers, 1993)
Proceedings of the Seminar on Architectural Conservation, held at Dhaka, Bangladesh, April 17, 1993.